Pregnant women's perceptions of drug use during pregnancy and its implications for the mother and fetus - Nurul Hidayati; Eka Mardiana Afrilia; Olyvia Rosalia (Oshada, 2025)
Pregnancy is a critical phase that demands careful attention to maternal health and well-being. However, the use of medication during pregnancy remains a controversial issue, often accompanied by confusion and fear. This study aims to explore pregnant women’s perceptions of drug use, assess their level of knowledge regarding drug safety, and examine the implications of these perceptions for maternal and fetal health. A quantitative cross-sectional design was employed with 120 pregnant women as respondents, selected through purposive sampling. Data were collected via structured questionnaires and analyzed using descriptive statistics and chi-square tests. The results revealed that 68.3% of respondents had negative perceptions of drug use during pregnancy, and 52.5% had low knowledge about medication safety. A significant relationship was found between perception and adherence to prescribed medication (p = 0.004). The findings highlight the urgent need for improved health education and counseling to ensure the safe and effective use of medication during pregnancy. Strengthening the role of healthcare providers in delivering accurate information can reduce unnecessary risks to both mothers and their unborn children.